Analisis Sebab Pelanggaran Pada Penerapan Prosedur Pemberhentian Perangkat Desa - Fajri, Naura Nurul; Azizah, Aulia Nur; Putra P, Andika Ivan; Hakim, Sholihul (Media Hukum Indonesia (MHI), 2024)
This research aims to analyze the mechanism for terminating village officials based on state administrative law sources. The dismissal of village officials is part of the village government system which has the authority to assist the village head in formulating policies and coordinating which is supported by secretaries in implementing policies in the form of technical implementation and regional elements. This research uses a qualitative approach with a case study method in several villages that implement a mechanism for discontinuing village officials. Data was collected through interviews with village officials, stopped village officials, and the community, as well as document analysis. The results of the research show that the slow procedure for terminating village officials is caused by several factors, one of which is low understanding of existing regulations, in addition to local political factors and the community's powerlessness in monitoring and enforcing the rules. This research provides an understanding of the need to increase the structural capacity of village officials in understanding regulations regarding the mechanisms for establishing and discontinuing village structures, as well as the need to improve transparent systems.